2015
DOI: 10.1097/hjh.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

The role of blood pressure, body weight and fat distribution on left ventricular mass, diastolic function and cardiac geometry in children

Abstract: Blood pressure values and hypertension are independently associated with an increase of cardiac mass and the presence of cardiac hypertrophy. Obesity and waist circumference, but not hypertension, are associated with a worsening of diastolic function, whereas only hypertensive children show high prevalence of concentric remodeling. Blood pressure and body weight and fat distribution have an independent and different impact on left ventricular structure and function in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 61 publications
3
64
0
1
Order By: Relevance
“…This decrease depends mainly on the peripheral vascular resistance and will represent the efficiency of the vasodilator mechanisms. 8,21,22 Corroborating the studies of Franz et al 12 we observed that changes in lifestyle are closely related to improvements in the cardiovascular system.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This decrease depends mainly on the peripheral vascular resistance and will represent the efficiency of the vasodilator mechanisms. 8,21,22 Corroborating the studies of Franz et al 12 we observed that changes in lifestyle are closely related to improvements in the cardiovascular system.…”
Section: Discussionsupporting
confidence: 64%
“…8,21,22 It is important to note that decreases in BP, HR and DP even in small magnitudes, promote large reductions in the rate of cardiovascular complications and general mortality. 23 The scientific literature shows that the physical exercise, present in the interdisciplinary therapy, promotes a decrease of the BP values in a chronic way.…”
Section: Discussionmentioning
confidence: 99%
“…Matteucci et al reported that in children with chronic renal insufficiency, the risk of LVH was four-fold greater in boys than in girls [27] and Meisinger et al found that men with CKD had higher concentrations of urinary albumin and greater cardiovascular risk than women [33]. Concentric LVH is believed to result primarily from hypertension and increased afterload [34]. In the present study, men had significantly higher values of BP and FPG, so it was quite possible for them to have greater aortic stiffness and lower total arterial compliance.…”
Section: Discussionmentioning
confidence: 99%
“…These reports describe a positive relationship of obesity with cardiac mass that appears to be independent of BP. 8,9 …”
Section: Introductionmentioning
confidence: 99%